BOOK REVIEW: Diana Dumitru, “Vecini în vremuri de restrişte: stat, antisemitism şi Holocaust în Basarabia şi Transnistria”, Iaşi: Polirom, 2019 - CRAIOVEANU, Flavia Elena (Studia Universitatis Babeș-Bolyai Historia, 2019)
This valuable book explores the circumstances of Jewish communities in Transnistria and Bessarabia during the tumultuous geopolitical changes that occurred at the beginning of the 20th century. Through her interview-based research, Diana Dumitru has been trying to see what determined Bessarabian civilians to massacre their Jewish neighbours during the Holocaust, while Transnistrian civilians were rather inclined to risk their lives for saving their Jewish counterparts. It is a book that looks critically and comparatively at two different regions: one that carries massacres, and one that shows compassion. The main argument of the book is that the relatively short period of two decades, during which each region had different administrations, policies, and public discourses, had such a great impact upon the civilian population, that it drove one group to gruesomely dehumanise and murder their neighbours, and the other to acknowledge the victim and act with compassion. The first of its six chapters deals with the situation of the Jewish population during the Russian czarist empire, moving on, in the second and third chapter, to how Jews were perceived during the interwar period in Romanian Bessarabia, and in Soviet Transnistria respectively. In the fourth and fifth chapter, the author looks at the attitudes of civilians towards Bessarabian Jews during the Holocaust, and Transnistrian Jews during the Romanian occupation, leaving the sixth chapter for conclusions and remarks. The book also provides illustrations, an index of names, as well as an ample bibliography.